EFFECTS OF LACTOBACILLUS PLANTARUM ON THE AKT/ENOS CARDIAC PATHWAY IN RATS WITH FRUCTOSE-INDUCED METABOLIC SYNDROME - Kursun, Oznur Ece Durmaz; Yalim, Goknur; Demirel, Murside Ayse; Erten, Fusun; Şahin, Kazım; Akar, Fatma (Poznan Univ Life Sciences, 2025)
Background. This study investigated the effects of Lactobacillus plantarum supplementation on the Akt/eNOS pathway in the cardiac tissue of rats subjected to a fructose-rich diet, which induced metabolic syndrome. Materials and methods. Twenty-two male Wistar albino rats were randomly assigned to three groups: (1) control, (2) fructose, and (3) fructose +/- L. plantarum. Rats in the fructose group were administered a 20% fructose solution in their drinking water for 15 weeks. In the L. plantarum-treated group, the probiotic was administered via gastric gavage at a daily dose of 1x109 CFU/mL/100 g during the final six weeks of the study. Results. The administration of Lactobacillus plantarum resulted in a significant increase in the levels of Akt (p < 0.0001), IRS-1 (p = 0.0113), mTOR (p < 0.0001), eNOS (p < 0.0001), and SIRT1 (p = 0.0031) in the cardiac tissue of rats compared to the fructose group. Moreover, a marked reduction in iNOS, NF-kappa B, and TNF-alpha levels (p < 0.0001) was observed, highlighting the potential of L. plantarum to counteract the adverse effects of fructose consumption. Conclusion. The findings of this study suggest that L. plantarum has the potential to reduce inflammation in the heart, enhance insulin sensitivity via the Akt/eNOS pathway, and protect against cardiovascular diseases associated with metabolic syndrome.
Keywords: metabolic syndrome; Lactobacillus plantarum; Akt; eNOS; fructose; insulin